2017
DOI: 10.1186/s13048-017-0355-y
|View full text |Cite
|
Sign up to set email alerts
|

Racial health disparities in ovarian cancer: not just black and white

Abstract: Ovarian cancer (OC) is the most lethal gynecological malignancy, which disproportionately affects African American (AA) women. Lack of awareness and socioeconomic factors are considered important players in OC racial health disparity, while at the same time, some recent studies have brought focus on the genetic basis of disparity as well. Differential polymorphisms, mutations and expressions of genes have been reported in OC patients of diverse racial and ethnic backgrounds. Combined, it appears that neither g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 86 publications
(101 reference statements)
1
32
0
Order By: Relevance
“…In-keeping with a less deprived population, our women had a lower average BMI and were less deprived than the general population [3]. Non-White ethnicity has previously been shown to adversely affect stage at diagnosis [32]. However, the high proportion of White women in the cohort (97.6%,~5% higher than reported in England and Wales 2011 census data [19]) meant that it was not possible to investigate this.…”
Section: Limitationsmentioning
confidence: 82%
“…In-keeping with a less deprived population, our women had a lower average BMI and were less deprived than the general population [3]. Non-White ethnicity has previously been shown to adversely affect stage at diagnosis [32]. However, the high proportion of White women in the cohort (97.6%,~5% higher than reported in England and Wales 2011 census data [19]) meant that it was not possible to investigate this.…”
Section: Limitationsmentioning
confidence: 82%
“…The existing literature supports the hypothesis that the risk of all-cause mortality in African American OC patients is roughly 1.3 times higher when compared to Caucasian women with OC, even when the access to care is equal [15] . The mortality rates have increased specifically for African American populations over time [15,16] . A study conducted by Srivastava et al [16] demonstrated that from 1992 to 2008 the 5-year survival rates for Caucasian women rose from 40.7% to 45%, yet 5-year survival rates for African American women declined over that same time period from 47.9% to 40.3%.…”
Section: Disparities In the Survival And Experience Of Oc Patientsmentioning
confidence: 99%
“…The mortality rates have increased specifically for African American populations over time [15,16] . A study conducted by Srivastava et al [16] demonstrated that from 1992 to 2008 the 5-year survival rates for Caucasian women rose from 40.7% to 45%, yet 5-year survival rates for African American women declined over that same time period from 47.9% to 40.3%. A similar study found that the 5-year survival rate for African American women had fallen to 36% from 2006 to 2012, while all races combined had a 45% 5-year survival rate, with Caucasian women having the highest 5-year survival rate at 46% [16] .…”
Section: Disparities In the Survival And Experience Of Oc Patientsmentioning
confidence: 99%
“…Racial disparities in ovarian cancer care are well documented at all stages of the care continuum . Access to care is one key component of high‐quality cancer care that may explain differences in ovarian cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…3 Cancer December 15, 2019 Racial disparities in ovarian cancer care are well documented at all stages of the care continuum. 4,5 Access to care is one key component of high-quality cancer care that may explain differences in ovarian cancer treatment. Although health insurance and socioeconomic status affect access to care, these factors alone fail to account for racial disparities in ovarian cancer treatment.…”
Section: Introductionmentioning
confidence: 99%